2017
DOI: 10.3899/jrheum.170170
|View full text |Cite
|
Sign up to set email alerts
|

CXCL10 and TRAIL Are Upregulated by TXNDC5 in Rheumatoid Arthritis Fibroblast-like Synoviocytes

Abstract: Downregulation of TXNDC5 could contribute to RASF antiangiogenic and proapoptotic features through the suppression of CXCL10 and TRAIL (tumor necrosis factor-related apoptosis-inducing ligand).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…TXNDC5 contributes to abnormal RA FLS proliferation, migration and IL-6 production by inhibiting IGFBP1 expression 34 . Downregulation of TXNDC5 could contribute to RA FLS antiangiogenic and proapoptotic features through the suppression of CXCL10 and TRAIL 35 . Further, TXNDC5 synergizes with heat shock cognate 70 protein (HSC70) to exacerbate the inflammatory phenotype of RA FLS through NF-κB signaling 36 .…”
Section: Discussionmentioning
confidence: 99%
“…TXNDC5 contributes to abnormal RA FLS proliferation, migration and IL-6 production by inhibiting IGFBP1 expression 34 . Downregulation of TXNDC5 could contribute to RA FLS antiangiogenic and proapoptotic features through the suppression of CXCL10 and TRAIL 35 . Further, TXNDC5 synergizes with heat shock cognate 70 protein (HSC70) to exacerbate the inflammatory phenotype of RA FLS through NF-κB signaling 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Downregulation of TXNDC5 could contribute to RA FLS antiangiogenic and proapoptotic features through the suppression of CXCL10 and TRAIL (33). Further, TXNDC5 synergizes with heat shock cognate 70 protein (HSC70) to exacerbate the inflammatory phenotype of RA FLS through NF-κB signaling (34).…”
Section: Discussionmentioning
confidence: 99%
“…As for CXCL10, markedly elevated protein levels were also detected in PBOV1 -overexpressed THP-1 supernatants. The pro-inflammatory chemokine CXCL10 has been reported to attract activated macrophages, T cells, and NK cells to the site of inflammation and is upregulated in autoimmune diseases, including RA [ 38 , 39 , 40 , 41 , 42 ]. It is suggested that CXCL10 increases the migration of inflammatory cells via CXCR3-mediated ERK activation and stimulates the production of osteoclastogenic cytokines in CD4+ T cells, resulting in bone destruction in RA [ 43 ].…”
Section: Discussionmentioning
confidence: 99%